Sistem Pendukung Keputusan Pemberian Bonus Karyawan Menggunakan Metode Analytical Hierarchy Process (Ahp) Dan SimpleAdditive Weighting (Saw) - setiyaki wicaksono, bagas; apriyanto, budi (Liaison Journal of Engineering, 2024)
Kalava Studio is an Information Technology company that is experiencing problems in the process of giving employee bonuses because manual calculations are time consuming and risky of errors. Employees are considered a key factor in a company's progress, and bonuses are an important incentive to improve their performance. Therefore, this research proposes the development of a decision support system (DSS) using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods to facilitate decision making regarding employee bonuses. This research involves three employee performance evaluation criteria, namely work results, attendance, and diligence. It is hoped that the combination of these two methods can overcome the complexity of decision making in an effective and efficient manner, helpthe Founder of Kalava Studio in determining employee bonuses objectively, and increase efficiency in human resource management. Keywords: Kalava Studio, Employee Bonuses, Decision Support Systems, Analytical Hierarchy Process (AHP), Simple Additive Weighting (SAW)